A Pesquisa sobre o ensino de probabilidade e estatística no Brasil: Um exercício de metacompreensão - Geromel Meneghetti, Renata C. [UNESP]; De Fátima Batistela, Rosemeire [UNESP]; Viggiani Bicudo, Maria Aparecida [UNESP] (My University, 2011)
This article presents an exercise in meta-comprehension of what has been researched on teaching probability and statistics in Brazil. This research was based on the work on this subject presented in the third International Symposium for Research in Mathematics Education (III SIPEM). Articles were selected from the proceedings of the event analyzed hermeneuticly according to the procedures of phenomenology. We observed no evidence of clustering of research on this topic in terms of region or institutions, and we also emphasize that research on the teaching of Probability and Statistics needs to advance toward a theoretical discussion that transcends the subjects being studied and makes broader and deeper links between theory and practice. Findings also indicate that this sub-area of research in mathematics education is in the process of constituting itself.
Research on the teaching of probability and statistics in brazil: An exercise in meta-comprehension
Keywords: Mathematics Education; Phenomenology; Probability and Statistics; Research and Teaching